New Insights into the Controls and Mechanisms of Plankton Productivity in Coastal Upwelling Waters of the Northern California Current System - Raphael Kudela; Neil Banas; John Barth; Elizabeth Frame; David Jay; John Largier; Evelyn Lessard; Tawnya Peterson; Andrea Vander Woude (Oceanography, 2008)

Intrinsic growth and microzooplankton grazing on toxigenic Pseudo‐nitzschia spp. diatoms from the coastal northeast Pacific - M. Brady Olson; Evelyn J. Lessard; Lessard Cochlan; Vera L. Trainer (Limnology and Oceanography, 2008)
We investigated the population ecology of toxigenic diatoms within the genus Pseudo‐nitzschia on the Pacific Northwest coast during 2003, 2004, and 2005. Pseudo‐nitzschia spp. were widespread and abundant across the region, and the maximum density reached at our experimental stations was ~7 × 10 6 cells L ‐1 . Pseudo‐nitzschia spp. biomass did not correlate with total phytoplankton biomass, indicating that the growth response and/or mortality rate of Pseudo‐nitzschia spp. were dissimilar to other phytoplankton. In dilution experiments across wide‐ranging ocean conditions, Pseudo‐nitzschia spp. intrinsic growth rates were moderate to high (mean = 0.97 d −1 , range 0.24 d −1 to 2.30 d−1 , n = 36), and they were consistently higher than the corresponding growth rates of the aggregate 5‐mm chlorophyll a (Chl a ) communities. Pseudo‐nitzschia spp. growth was predicted by irradiance and temperature but not ambient nitrate concentration, whereas both Chl a size fractions showed dependence upon nitrate for growth. Microzooplankton grazing rates on Pseudo‐nitzschia spp. were moderate (mean = 0.32 d ‐1 , range 0.00 d ‐1 to 1.70 d ‐1 , n = 36); they were nearly always lower than corresponding Pseudo‐nitzschia spp. intrinsic growth, significantly lower than the grazing rates on the a size fraction, and comparable to grazing rates on the >5‐mm Chl a size fraction. Our results show that the strong competitive fitness of Pseudo‐nitzschia spp. results more from expression of characteristics that enable sustained high growth during variable and unfavorable conditions than from intrinsic adaptations that reduce grazing mortality.

Nitrate : phosphate ratios and Emiliania huxleyi blooms - Evelyn J. Lessard; Agostino Merico; Toby Tyrrell (Limnology and Oceanography, 2005)
It has been hypothesized that phosphate limitation, classically indicated by NO 3 : PO 4 ratios >16, is one of the critical factors allowing the coccolithophorid Emiliania huxleyi to bloom. This hypothesis is based on physiological studies showing that E. huxleyi has an exceptionally high affinity for orthophosphate and is able to use organic phosphate. Indeed, E. huxleyi has been found to bloom at high NO 3 : PO 4 ratios in some mesocosm studies and in the oceanic northeast North Atlantic. Recent E. huxleyi blooms on the southeastern Bering Sea shelf, however, occurred under low NO 3 : PO 4 conditions, which is indicative of nitrogen rather than phosphorus stress. A review of field studies of blooms where nitrate and phosphate were measured indicates that NO 3 : PO 4 was in fact frequently low. A survey of most of the areas of the world ocean where satellite‐detected E. huxleyi blooms occur also shows that NO 3 : PO 4 ratios are generally low. These observations suggest that E. huxleyi is able to exploit situations where either phosphorus or nitrogen is limiting to competing species. They also indicate that attention should be directed to examining organic nitrogen, organic phosphorus, and ammonium during E. huxleyi blooms to better understand the role macronutrients play in these blooms.

The Northeast Pacific GLOBEC Program: Coastal Gulf of Alaska - Thomas Weingartner; Kenneth Coyle; Bruce Finney; Russell Hopcroft; Terry Whitledge; Richard Brodeur; Michael Dagg; Edward Farley; Dale Haidvogel; Lew Haldorson; Al Hermann; Sarah Hinckley; et al. (Oceanography, 2002)

Carbon to volume relationships for dinoflagellates, diatoms, and other protist plankton - Susanne Menden-Deuer; Evelyn J. Lessard (Limnology and Oceanography, 2000)
Cellular carbon and nitrogen content and cell volume of nutritionally and morphologically diverse dinoflagellate species were measured to determine carbon to volume (C:vol) and nitrogen to volume (N:vol) relationships. Cellular C and N content ranged from 48 to 3.0 × 10 4 pgC cell −1 and 11 to 2,656 pgN cell −1 for cells ranging in volume from 180 to 2.8 × 10 5 µm 3 . C and N density in dinoflagellates decreased significantly with increasing cell volume. C:N ratios ranged from 3.44 to 6.45. C:vol and N:vol in dinoflagellates are significantly related as expressed by the equations pgC cell −1 = 0.760 × volume 0.819 and pgN cell −1 = 0.118 × volume 0.849 . Previously published data were combined to compare C:vol relationships in different phylogenetic protist groups, including chlorophytes, chrysophytes, prasinophytes, and prymnesiophytes. Our analysis indicated differences between the C:vol relationships available for ciliates. A new C:vol relationship for diatoms was established (pgC cell −1 = 0.288 × volume 0.811 ). Dinoflagellates are significantly more C dense than diatoms. Except for diatoms, we found few significant differences between C:vol relationships of different phylogenetic groups. Consequently, one C:vol relationship for taxonomically diverse protist plankton excluding diatoms was determined (pgC cell −1 = 0.216 × volume 0.939 ). In the combined data set, carbon density was not constant but decreased significantly with increasing cell volume. Using constant C:vol conversion factors for plankton over large size ranges will cause systematic errors in biomass estimates.